Imaging Collagen in Intact Viable Healthy and Atherosclerotic Arteries Using Fluorescently Labeled CNA35 and Two-Photon Laser Scanning Microscopy - Remco T.A. Megens; Mirjam G.A. oude Egbrink; Jack P.M. Cleutjens; Marijke J.E. Kuijpers; Paul H.M. Schiffers; Maarten Merkx; Dick W. Slaaf; Marc A.M.J. van Zandvoort (Molecular Imaging)
We evaluated CNA35 as a collagen marker in healthy and atherosclerotic arteries of mice after both ex vivo and in vivo administration and as a molecular imaging agent for the detection of atherosclerosis. CNA35 conjugated with fluorescent Oregon Green 488 (CNA35/OG488) was administered ex vivo to mounted viable muscular (uterine), elastic (carotid), and atherosclerotic (carotid) arteries and fresh arterial rings. Two-photon microscopy was used for imaging. CNA35/OG488 labeling in healthy elastic arteries was compared with collagen type I, III, and IV antibody labeling in histologic sections. For in vivo labeling experiments, CNA35/OG488 was injected intravenously in C57BL6/J and apolipoprotein E −/− mice. Ex vivo CNA35/OG488 strongly labeled collagen in the tunica adventitia, media, and intima of muscular arteries. In healthy elastic arteries, tunica adventitia was strongly labeled, but labeling in tunica media and intima was prevented by endothelium and elastic laminae. Histology confirmed the affinity of CNA35 for type I, III, and IV collagen in arteries. Strong CNA35/OG488 labeling was found in atherosclerotic plaques. In vivo applied CNA35/OG488 minimally labeled the tunica intima of healthy carotid arteries. Atherosclerotic plaques in apolipoprotein E −/− mice exhibited large uptake. CNA35/OG488 imaging in organs revealed endothelium as a limiting barrier for in vivo uptake. CNA35/OG488 is a good molecular imaging agent for atherosclerosis.